KINERJA BANK UMUM SYARIAH BERDASARKAN MAQASHID SYARIAH INDEX - Wahyuningsih, Wahyuningsih; Maryati, Maryati; Birton, Muhammad Nur Abdullah (Universitas Muhammadiyah Palembang, 2024)
This study aims to measure the performance of Sharia Commercial Banks (BUS) using the Maqashid Syariah Index (MSI), and compare the results using the capital structure of BUS. This study applies quantitative and comparative -descriptive methods based on data from the annual financial statements of 12 BUS Indonesia for the 2021-2022. Data analysis was conducted using three MSI indicators (ratios), namely educating individuals, upholding justice, and promoting prosperity, as the basis for evaluation. The results showed that in 2021, there were five BUS that obtained results above 0.1; in order, namely BTPNS, BAS, BMS, BSI, and BCAS. In 2022, there are BUS goals that obtain results above 0.1, respectively, namely BTPNS, BMS, BAS, BCAS, BSI, BNTB, BJBS. Measured by KBMI, BTPNS (KBMI 2) ranked 1st two years in a row; while BSI (KBMI 3) is only ranked 4th (2021), even in 2022 it fell to rank 5 (2022). This means that the capital structure (KBMI) is not positively correlated with MSI's performance.